Gausemycins A, B: Cyclic Lipoglycopeptides from Streptomyces sp. Issue 34 (22nd June 2021) - Tyurin, Anton P.; Alferova, Vera A.; Paramonov, Alexander S.; Shuvalov, Maxim V.; Kudryakova, Gulnara K.; Rogozhin, Eugene A.; Zherebker, Alexander Y.; Brylev, Vladimir A.; Chistov, Alexey A.; Baranova, Anna A.; Biryukov, Mikhail V.; Ivanov, Igor A.; et al.
Abstract: We report a novel family of natural lipoglycopeptides produced by Streptomyces sp. INA‐Ac‐5812. Two major components of the mixture, named gausemycins A and B, were isolated, and their structures were elucidated. The compounds are cyclic peptides with a unique peptide core and several remarkable structural features, including unusual positions of d ‐amino acids, lack of the Ca 2+ ‐binding Asp‐X‐Asp‐Gly (DXDG) motif, tyrosine glycosylation with arabinose, presence of 2‐amino‐4‐hydroxy‐4‐phenylbutyric acid (Ahpb) and chlorinated kynurenine (ClKyn), and N‐acylation of the ornithine side chain. Gausemycins have pronounced activity against Gram‐positive bacteria. Mechanistic studies highlight significant differences compared to known glyco‐ and lipopeptides. Gausemycins exhibit only slight Ca 2+ ‐dependence of activity and induce no pore formation at low concentrations. Moreover, there is no detectable accumulation of cell wall biosynthesis precursors under treatment with gausemycins. Abstract : A family of natural lipoglycopeptides produced by actinobacteria and named gausemycins showed pronounced activity against Gram‐positive bacteria. Gausemycins have a unique peptide core that includes 2‐amino‐4‐hydroxy‐4‐phenylbutyric acid (Ahpb), chlorinated kynurenine (ClKyn), O ‐arabinosylated tyrosine, and N δ ‐acylated ornithine residues (see structure). Mechanistic studies highlight significant differences to known antibiotics.